2014
DOI: 10.1111/jan.12546
|View full text |Cite
|
Sign up to set email alerts
|

Between invisible defects and visible impact: the life experiences of adolescents and young adults with congenital heart disease

Abstract: As patients with congenital heart disease transition from adolescence into adulthood, they must learn about their disease, overcome frustration and anxiety and develop self-care strategies for coexisting with congenital heart disease. Results of this study may serve as clinical care guidelines for adolescents and young adults with congenital heart disease and give a reference for developing transitional intervention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 30 publications
(50 reference statements)
2
27
0
2
Order By: Relevance
“…Twelve out of 15 participants described experiencing negative mood and in some cases clinically diagnosed depression and suicidal thoughts as a result of their condition/s, and eight reported experiencing anxiety and fear for the future. This complements and expands on earlier findings with predominantly older adults and/or amongst individuals with specific individual LTCs . Nine out of 15 participants made comparisons between their former ‘well’/’healthy’ self and their current ‘ill’/‘sick’ self, with longing for their past self and grieving lost parts of their identity (although it is important to note that this sub‐theme is only applicable to young adults diagnosed from birth/infancy, perhaps excluding for example congenital illnesses such as cystic fibrosis, where there is no prior period of ‘wellness’ or perceived ‘normality’).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Twelve out of 15 participants described experiencing negative mood and in some cases clinically diagnosed depression and suicidal thoughts as a result of their condition/s, and eight reported experiencing anxiety and fear for the future. This complements and expands on earlier findings with predominantly older adults and/or amongst individuals with specific individual LTCs . Nine out of 15 participants made comparisons between their former ‘well’/’healthy’ self and their current ‘ill’/‘sick’ self, with longing for their past self and grieving lost parts of their identity (although it is important to note that this sub‐theme is only applicable to young adults diagnosed from birth/infancy, perhaps excluding for example congenital illnesses such as cystic fibrosis, where there is no prior period of ‘wellness’ or perceived ‘normality’).…”
Section: Discussionsupporting
confidence: 63%
“…A few studies have been conducted with young adults (with chosen age ranges of young adulthood varying between 14 and 45). Studies have found that cystic fibrosis, congenital heart disease and diabetes are associated with anxiety, depression, fear and worry; and that young adults with various LTCs are statistically more likely to experience anxiety and/or depression than healthy participants (eg Ref …”
Section: Introductionmentioning
confidence: 99%
“…Asking the adolescent to give a short summary in the end of the meeting can be one way to establish that. Inaccurate knowledge about the CHD might lead to unnecessary restrictions [48], avoidance of deeper relations [6] and uncertainty [2, 4, 5, 22]. The majority of the adolescents in our study said that they had general knowledge about their CHD; something they learned over the years in the paediatric setting.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, several studies indicate that adolescents do not feel included and involved in the preparation before the transfer [13, 57, 58, 63], which also may increase the risk of loss of follow-up after transfer to adult care [6]. …”
Section: Introductionmentioning
confidence: 99%
“…In fact, the adolescence is a crucial phase for the formation of the personality [7], during which the CHD adolescents have to face with the consequences of their disease and the need to be adherent with their follow-up indications [10]. Moreover, during the transition into adulthood, CHD adolescents could be exposed to many psychological issues related to their development of self-identity, self-esteem and self-image [8] and they should learn about their disease, overcoming frustration and anxiety and developing self-care strategies [9]. For this reason, the recent clinical research focused to explore the peculiarity of the transition period synthesis.…”
Section: Introductionmentioning
confidence: 99%